Low genetic diversity and no genetic differentiation between maleo hatched at coastal and inland nesting grounds in North Sulawesi, Indonesia - Andie Wijaya Saputra; Pramana Yuda (Society for Indonesian Biodiversity, 2020)
Abstract. Saputra AW, Yuda P. 2020. Low genetic diversity and no genetic differentiation between maleo hatched at coastal and inland nesting grounds in North Sulawesi, Indonesia. Biodiversitas 21: 4772-4777. Maleo Senkawor (Macrocephalon maleo), an endemic and endangered bird of Sulawesi (Indonesia), is burrow-nesting megapodes that incubate its eggs in communal nesting sites in soils heated by sun on beaches and by volcanic activity in inland. The aims of this study were to assess genetic diversity of the Maleo and examine whether those which have different nesting sites have become genetically differentiated. In total, 24 eggshell membranes of Maleo were collected from Tanjung Binerean (coastal nesting ground) and Tambun (inland nesting ground), and the DNA was extracted using silica spin-column kit. PCR was applied to amplify the hypervariable region 1 (HV1) and partial mtDNA control region of HV2 using a specific primer set designed for Maleo. The PCR products were sequenced, resulted in 612 bp, and showed 9 polymorphic sites and 9 haplotypes (H). Further sequences analysis suggested that there was no genetic differentiation between coastal nesting population and inland nesting population (Fst = 0.0009; P = 0.431). As expected, the genetic diversity of Maleo was relatively low (coastal nesting population, Hd: 0.727270, ?: 0.002377 and inland nesting population Hd: 0.848480, ?: 0.002203).